2015
DOI: 10.1007/s10585-015-9700-y
|View full text |Cite
|
Sign up to set email alerts
|

HES1 promotes metastasis and predicts poor survival in patients with colorectal cancer

Abstract: Hairy enhancer of split-1 (HES1) is a transcriptional target of the Notch pathway, and a high level of HES1 is regarded as a marker of activated Notch. The aim of the study was to investigate the role of HES1 in colorectal cancer progression. We used tissue microarrays to analyze the expression and clinical significance of HES1 in 320 colorectal cancer samples. Stable overexpression and knockdown of HES1 were established in three colorectal cancer cell (CRC) lines (RKO, HCT8 and LOVO). We investigated the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
3
32
0
1
Order By: Relevance
“…We observed that C-B and C-I treatment downregulated the expression Notch receptors, ligands, γ-secretase complex and target genes. Dysregulation of Notch signaling has been correlated with poor survival, CSC phenotype and EMT resulting in tumor progression in colon cancer 47 . Notch 1 and 2, as well as their ligands, are dysregulated in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that C-B and C-I treatment downregulated the expression Notch receptors, ligands, γ-secretase complex and target genes. Dysregulation of Notch signaling has been correlated with poor survival, CSC phenotype and EMT resulting in tumor progression in colon cancer 47 . Notch 1 and 2, as well as their ligands, are dysregulated in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that HES1 affects cell proliferation and differentiation during embryogenesis, maintenance of stem cells, and the malignancy and maintenance of tumor cells (13). Overexpression of HES1 is associated with the development of several types of cancer, including lung cancer, cervical cancer, prostate cancer, oral squamous cell carcinoma, pancreatic cancer, colon carcinoma, and ovarian cancer (14)(15)(16). The function of HES1 and its involvement in the regulation in malignant breast cancer remain to be fully elucidated; therefore, it is necessary to investigate its function and underlying mechanisms in breast cancer proliferation and metastasis.…”
Section: Lutein Inhibits Proliferation Invasion and Migration Of Hypmentioning
confidence: 99%
“…Up-regulation of NOTCH1, JAG ligands and HES1 in CRC cell lines results in the increased expression of the EMT/stemness-associated proteins: CD44, SLUG, and SMAD3 (7,8). High expression of HES1 is significantly correlated with distal metastasis at diagnosis, and unfavorable prognostic outcome for CRC patients (9). Activation of NOTCH signaling also protects CSCs from apoptosis (10).…”
Section: Introductionmentioning
confidence: 99%